Lampungic Maintenance in Urban Areas: The Differences Based on Student’s Response - Wuri Syaputri; Njaju Jenny Malik Malik; Frans Asisi Datang (Universitas Lancang Kuning, 2022)
Lampungic is a local language used in Lampung province. Besides Lampungic, Lampung province also has many speakers who speak other languages such as Bali language, Basemah language, Bugis language, Java Language, and Sunda language. While the Lampungic has four dialects, namely Abung, Pesisir, Pubian, and Komering dialects. The Abung dialect is spread across the districts of North Lampung, Way Kanan, Central Lampung, Metro City, and East Lampung. The Pesisir Dialect is located in the districts of Pringsewu, Tanggamus, South Lampung, West Lampung, Tulang Bawang, West Pesisir, Bandar Lampung City, and Pesawaran District. The Pubian dialect is spread in the areas of South Lampung, Central Lampung, and North Lampung. While the Komering dialect is in the speech community of the North Lampung region. This study is using descriptive quantitative method. The quantitative used to get the different results in Lampungic used in Bandar Lampung city (the city close to the government center) and Metro City (the city far from the government center). The quantitative data result got from SPSS with Mann Whitney formula. The descriptive is used to describe the data count result based on respondents’ answers. Respondents were the students from primary school until university who speaks Lampungic and leave in Bandar Lampung and Metro cities. The result shows that language maintenance has no differences between Bandar Lampung and Metro cities.